Comparison of electric motors used in electric vehicle propulsion system - Khalid S. Mohammad; Aqeel S. Jaber (Institute of Advanced Engineering and Science, 2022)
Now days, it is vital to use electric vehicles (EVs) instead of traditional cars with internal combustion engines (ICEs) in order to reduce the high level of pollution in the environment, and many researchers are investigating the possible improvements on these vehicles. The main component of EVs is the electric motor and the selection of a motor with high efficiency, excellent dynamic response and high starting torque has a strong effect on the performance of EVs. In addition to that a reasonable price for the electric motor is required. This work focuses on the selection of the most suitable electric motor for EVs. Therefore a detailed study to compare between the performance of the major types of electric motors that are used in EVs is addressed in this paper. The results of this comparative study is tabulated and by careful consideration for all these results, the appropriate electric motor for EVs has been chosen. From the other hand, the artificial intelligent (AI) techniques play a crucial role in the EVs technologies, and several kinds of AI techniques used in EVs applications are overviewed in this work.